Analisis Faktor-Faktor Yang Menentukan Kinerja Pegawai Pada PD Parkir Kota Denpasar - Sudarsana, A.A Putu; Sriathi, A.A Ayu (E-Jurnal Manajemen, 2013)
Performance is the result of the work produced by the high and low quality employee performance will determine the survival of Denpasar in the PD parking services parking fees. The purpose of this study to examine the factors that determine the performance of employees in the PD parking Denpasar. Respondents of this study were 74 people. Exploratory factor analysis is used as analysis technique. The results shows that among 25 variables, obtained six factors that represent because it has the highest factor loading (1) information regarding the activities of the company, (2) workspace color settings, (3) training schedule, (4) dissent, (5 ) leadership assertiveness, and (6) discuss the problem. Factor information about the company's activities is the dominant factor determining the performance of the employee as having eigen value of 11.489                                 .                                                           Keywords: Employee Performance